PENGARUH KETERLAMBATAN PEMBAYARAN PAJAK KENDERAAN BERMOTOR TERHADAP PROSES PEMBERIAN BANTUAN KECELAKAAN OLEH PT JASA RAHARJA MALUKU - Imran Hatala (Juremi: Jurnal Riset Ekonomi, 2025)
This study aims to examine the effect of delayed motor vehicle tax payments on the accident compensation process carried out by PT Jasa Raharja Maluku. The Motor Vehicle Tax (PKB), which is paid concurrently with the Mandatory Contribution to Road Traffic Accident Fund (SWDKLLJ), serves as a crucial requirement for the disbursement of compensation to traffic accident victims. However, in practice, many vehicle owners delay tax payments, which negatively impacts the administrative procedures and delays the compensation process. This research uses a quantitative approach with a simple linear regression analysis technique. Data were collected through documentation, observation, and interviews with PT Jasa Raharja officials and from traffic accident claim records in Maluku. The findings show that delayed tax payments significantly influence the delay in the compensation process. The coefficient of determination (R²) of 0.555 indicates that 55.5% of the variation in the length of the compensation process can be explained by the delay in tax payments. In conclusion, late payment of motor vehicle taxes significantly slows down the accident compensation process by PT Jasa Raharja. Therefore, it is necessary to increase public awareness of timely tax compliance and strengthen coordination among related institutions to streamline the claim verification process.